Harmoni Keuangan Dalam Rumah Tangga: Meningkatkan Literasi, Pengelolaan, dan Sikap Keuangan - Sari, Nova Vurba; Goso, Goso; Duriani, Duriani (Universitas Muhammadiyah Pontianak, 2025)
This study aims to analyze the influence of financial literacy, financial management, and financial attitudes on household financial harmony. Using a quantitative approach with 100 housewives in North Luwu Regency, the data were analyzed using validity, reliability tests, and Structural Equation Modeling (SmartPLS). The findings reveal that financial literacy, management, and attitudes have both direct and indirect effects on financial harmony. This study implies that financial education plays an essential role in shaping positive financial behavior and attitudes, thereby improving household welfare and financial harmony.